The effect of the language and cultural differences of leaders in company policies on employee motivation : a study on a Japanese company - Akci, Anıl (My University, 2020)
Çalışma, Türkiye’de konumlanmış bir Japon şirketinin şirket politikalarını gözeterek çalışanlarından iş liderlerinin, genellikle Japon ya da Türk, liderlik kültürlerinin ve dil farklılıklarının çalışma motivasyonuna etkisini incelemiştir. Türkiye’de yer alan Japon şirketlerde yabancı dil kullananlar şirketin üst yönetim kademelerinde yer aldığı için inceleme ağırlıklı olarak yönetim kademesi üzerine yapılmıştır. Şirket politikaları şirketlerin planları ve hedefleri doğrultusunda ilkeleriyle hareket etmesini amaçlamaktadır. Bu ilkeler nezdinde politikalar uygulanırken liderlik kültür farklılıklarının çalışanların motivasyonuna etkisi gözlemlenmiştir. Motivasyonda temel amaç iş görenin istekli, verimli ve etkili çalışmasını sağlamaktır. Bunun için yöneticiler tarafından çeşitli özendirici araçlar kullanılır. İnsanı özel yaşamında ve iş yaşamında motive eden birçok faktör vardır. Ancak bu araçlar her yerde ve her zaman aynı etkiyi göstermezler. Bir kişi için özendirici olan araç bir diğeri için aynı anlamı taşımayabilir ve bu isteklendirme faktörleri her kişide değişiklik gösterir. Motivasyon yani isteklendirme ve tatmin kavramları arasında ortak nokta her iki kavramın da duygusal, kişisel ve öznel olmalarıdır. Japon halkı kendi resmi dilini kullanıyor olup Türkçe dilinden alfabe olarak da farklıdır. Kültür olarak da hem farklı coğrafya, farklı yönetim şekli, farklı din ve dil, farklı tarihe sahip olduğu için konulara yaklaşımlarında da farklılık gözlemlenebilir. Böyle farklı alfabe, kültür, bakış açılarına sahip bir ülkenin şirketlerinin farklı şirket politikalarıyla başka bir coğrafya geçmişine sahip kültürdeki şirketlere yatırım yapmasında zorluklar yaşanabilir. Tezin amacı ve hedefi Türkiye’ye yabancı sermaye ile yatırım yapılan, özellikle Japon şirketlerin Türkiye’de ikame eden Türk şirketleri satın alımları, şirketlerde şirket politikalarında yaşanan zorlukları kültür ve dil boyutunda incelemek ve ileride doğacak başka sermaye yatırımlarını kolaylaştırmasına katkıda bulunmaktır. Bu anlamda bir Japon şirket belirlenip anketlerle konulara değinilmiştir.

The study examined Turkey located Japanese company’s business leaders, mainly Japanese or Turkish employees, the effect of the motivation of cultural and language diversity taking into consideration of the company's policies’ applications. The examination was held for management positions in a Japanese company located in Turkey, since employees who speak foreign languages in management positions.Company policies aim to ensure that companies act in accordance with the principles that can be differentiated from company to company. In line with the applicability of these principles and policies, the impact of cultural differences on the motivation of employees was observed.The main purpose of motivation is to ensure that the employee works willingly, efficiently and effectively. Various incentive tools are used by administrators for this purpose. There are many factors that motivate people in private and business life. However, these tools do not have the same effect everywhere and at all times. The tool which is encouraging for one person may not have the same meaning for another. The factors that motivate employees vary from person to person. The common point between motivation and satisfaction is that both concepts are emotional, personal and subjective. The Japanese people use their official language and are also different from the Turkish language in alphabetical order. As the culture has different geography, different management style and language. There is a difference in their approach to the subjects. Companies of a country with such different alphabets, cultures and perspectives have difficulties in investing in companies with a different geographic past through different company policies. The purpose and objectives of the thesis to Turkey invested by foreign capital, especially those substituted in Turkey of Japanese companies, to investigate the difficulties experienced in companies in company policy and to contribute to the facilitation of further capital investment. In this sense, a Japanese company was identified and the survey was discussed in the results part of the study.
Keywords: belirsizlikten kaçınma; Business; culture; Çalışan motivasyonu; dil; dönüşümcü liderlik; Employee motivation; İşletme; kültür; language; leadership; liderlik; transformational leadership; uncertainty avoidance